Frost und Gedächtnis: "Das Eis-Schloss" von Tarjei Vesaas - Seiler, Thomas (Folia Scandinavica Posnaniensia, 2016)
Critics have interpreted Tarjei Vesaas’s novel The Ice Palace (1963) in psychological terms as a kind of rite-of-passage fable of two eleven-year-old girls, Siss and Unn. The latter dies in a magic Ice Palace short after their first meeting in Unn’s house. The novel’s plot is about how Siss is dealing with the loss. Other scholars put the emphasis on the folkloristic elements or read the text as an allegorical one, as a piece of art dealing with art. In the following article I would like to read The Ice Palace as a poetic treatise on the relationship between mourning, melancholy on the one hand and commemoration, memorialization on the other.